Prevention of propofol injection pain: Comparison between lidocaine and ramosetron - Dipali Singh; Sathyanarayan Jagannath; Shio Priye; Shivaprakash; Chandrashekar Kadli; Durgaprasad Reddy (Wolters Kluwer Medknow Publications, 2014)
Background: Propofol causes a high incidence of pain during intravenous (IV) injection. The aim of this randomized, placebo-controlled, double-blinded study was to determine whether pre-treatment with IV ramosetron, used for prophylaxis of postoperative nausea and vomiting (PONV), would reduce propofol-induced pain as an equivalent to lidocaine. Materials and Methods: Hundred and twenty American Society of Anesthesiologists grade (ASA) I and II patients were randomly assigned into three groups (40 in each). Group N received 2 ml of 0.9% saline, Group L received 2 ml of lidocaine, and Group R received 2 ml of ramosetron. Mid forearm was occluded manually before injection and released after 1 min and then propofol was injected over 5 s. Patients were observed and questioned 15 s later if they had pain in the arm and pain was scored on a four-point scale: 0 = no pain, 1 = mild pain, 2 = moderate pain, and 3 = severe pain. Unpaired Student's t-test and chi-square test/Fisher' exact test were used to analyze results. Results: The incidence of pain in groups N, L, and R were 65, 35, and 30%, respectively. Pain was reduced significantly in the groups L and R (P < 0.05). Two patients each in Groups L and R (5% each) had moderate and severe pain. This difference in pain was statistically insignificant, but when compared to Group N (25 and 30%, respectively) it was statistically significant. Conclusion: Pretreatment with ramosetron 0.3 mg and lidocaine 40 mg are equally effective in preventing pain from propofol injection.